Photogrammetric and laser scanning data integration - Mikrut, Sławomir (My University, 2009)
The subject of research included integration of laser scanning data with photogrammetric data, and an attempt at identifying the 'bottlenecks' in available technologies, and offering proposals for solving them. The research was conducted based on an exemplary facility, located in the Ethnographic Park of the Village Museum at Tokarnia, Poland. One of the museum exhibits, a windmill, was utilised as a test field, as there was a good access to it, as well as because of certain, expected complications related to processing parts of the windmill, such as e.g. penthouses. The research employed a Z-F Zoller-Fröhlich, model IMAGER 5006 laser scanner, a Rollei 6008 digital photogrammetric camera, a TCR 405 POWER prismless total station, RealWorks Survey Advanced, Photomodeler and Dephos software, as well as own algorithms, collected in the authorial feature extraction software (FES). In this paper, a certain pattern of integration of photogrammetric data with a point cloud was proposed. It was based on that pattern, that the exemplary project was developed. Also, an attempt was made at improving the quality of integration though the use of algorithms of sub-pixel edging of data, both in the digital image, and in the point cloud. The so-developed methodology is useful, not only when surveying historic buildings and structures. It can also be applied in the course of works related to the surveys of buildings, industrial facilities, boring towers, etc. Also known are non-typical applications of the method, which include e.g. the survey of a post- accident condition conducted by the police on the accident spot, as well as a whole array of applications of the air scanning, which (due to their extensive scope) have not been included in this paper. The completed experiments as well as data from the literature on the subject make it possible to declare that the results of the use of photogrammetry combined with laser scanning are promising. This is a quick and an efficient technology. Owing to scanning, we can obtain a very large amount of data, while photogrammetry provides radiometric data of a high quality. That combination seems to be indispensable in near future, and one may expect it will quickly be developing.

Przedmiotem badań była integracja danych ze skaningu laserowego z fotogrametrycznymi oraz próba znalezienia wąskich gardeł w dostępnych technologiach i propozycje ich rozwiązań. Badania wykonano na przykładowym obiekcie zlokalizowanym w Parku Etnograficznym Muzeum Wsi Kieleckiej w Tokarni. Wiatrak z Grzmucina posłużył jako pole testowe z racji dobrego dostępu oraz pewnych spodziewanych komplikacji w opracowaniu jego części, takich jak np. wiatrołapy. W badaniach wykorzystano skaner laserowy firmy Z-F Zoller-Fröhlich model IMAGER 5006, cyfrową kamerę fotogrametryczną Rollei 6008, tachimetr bezlustrowy TCR 405 POWER oraz oprogramowanie RealWorks Survey Advanced, Photomodeler, Dephos i własne algorytmy zebrane w programie FES (Feature Extraction Software). W niniejszym opracowaniu zaproponowano pewien schemat integracji danych fotogrametrycznych z 'chmurą punktów'. Na bazie tego schematu wykonano przykładowe opracowanie. Dokonano również prób poprawy jakości integracji przez zastosowanie algorytmów podpikselowego krawędziowania danych zarówno na obrazie cyfrowym, jak i w 'chmurze punktów'. Opracowana metodyka jest funkcjonalna nie tylko w inwentaryzacji obiektów zabytkowych. Może być również stosowana do prac związanych z inwentaryzacją budowlaną, przemysłową, wież wiertniczych itp. Znane są również nietypowe zastosowania, takie jak inwentaryzacja stanu powypadkowego dokonywana przez policję na miejscu wypadku oraz cały szereg zastosowań skaningu lotniczego, który w tym opracowaniu pominięto. Przeprowadzone eksperymenty oraz dane literaturowe pozwalają stwierdzić, że zastosowanie fotogrametrii wraz ze skanowaniem laserowym daje obiecujące wyniki. Jest to szybka i wydajna technologia. Dzięki skaningowi potrafimy otrzymać bardzo dużą ilość danych, a fotogrametria dostarcza wysokiej jakości danych radiometrycznych. Powiązanie obu tych dziedzin wydaje się konieczne i powinno być szybko rozwijane.
Integracja danych fotogrametrycznych z danymi pozyskanymi ze skaningu laserowego
Geomatics and Environmental Engineering
Keywords: laser scanning; photogrammetry; skaning laserowy; fotogrametria; feature extracting; krawędziowanie